The Cancer Diseases Evolution in Erbil Governate in The Period of 2013 – 2020: A Study in Medical Geography - Haval Kamal Hussein; Kamaran Ualy Mahmood (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
Cancer is a disease that, despite the differences in the types and causes of the disease, it is affected by all the ages and both genders , and many people around the world face death every year because of it, Till now the main reason is not known and could not be removed, cancer has been a disease throughout human life. The aim of the investigation is to investigate the development of cancer in Erbil province from 2013 to 2020. This study consists of four parts, starts within the framework of research theory, then discusses annual changes and monthly changes in cancer In Erbil governorate, the fourth part is special to the risk of cancer,for this purpose,the researcher used the survey form.The research has reached many results,the most obvious of which is the phenomenon of infection increases and may appear at every months of the year, breast cancer in a rate (%20.6)ahead of all cancer diseases ,smoking habits are among the most affected by lung cancers.